Critical Education Analysis Based on Creative Minority: Case Study at the Sekolah Pemikiran Islam PK IMM FAI UMY - Putra, Ramadhanur (Forum Akademisi dan Dosen Peneliti (FAST), 2026)
This study examines the critical education based on creative minority implemented by the School of Islamic Thought (SILAM), an alternative education program run by the Muhammadiyah Student Association (Ikatan Mahasiswa Muhammadiyah) student organization, Faculty of Islamic Studies, Muhammadiyah University of Yogyakarta. It examines its history, processes, and dynamics during 2020–2022, its role in students' intellectual development, and supporting and inhibiting factors in its implementation. This study employed a qualitative research design and a case study approach. Interviews were conducted with the founder or initiator of SILAM, the Chairperson of the 2020, 2021, and 2023 Activities, and two participants in each implementation year (one male and one female). Indirect observation and documentation were also conducted for data collection. The results of this study indicate that SILAM aims to provide a forum for students to strengthen their knowledge of philosophy, sociology, and Islamic thought. They have a Standard Operating Procedure (SOP) to regulate the implementation of SILAM. The majority of SILAM alumni feel the school has positively influenced their cognitive and social development. Several inhibiting and supporting factors influence SILAM's effectiveness each year.